2017
DOI: 10.1128/genomea.00242-17
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Two Hydrogenogenic Carboxydotrophic Bacteria, Carboxydocella sp. Strains JDF658 and ULO1, Isolated from Two Distinct Volcanic Fronts in Japan

Abstract: Hydrogenogenic carboxydotrophs may provide hydrogen as primary energy for the microbial community via carbon monoxide oxidation. To investigate the genetics of carbon monoxide metabolism, we report here the draft genome sequences of the hydrogenogenic carboxydotrophs Carboxydocella sp. strains JDF658 (2.60 Mbp; G+C content, 49.2%) and ULO1 (2.70 Mbp; G+C content, 48.8%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…At the Unagi-onsen hot spring (Southern Kyushu Island), we collected a total of 65 samples in May 2014, May 2015, November 2015, and December 2016 as a previous study suggested that Carboxydothermus species are abundant in this environment (Yoneda et al 2013a). In addition, we previously isolated the Carboxydocella strains ULO1 and JDF658 at Unagi-ike lake and the Jiunji-onsen hot spring, respectively (Fukuyama et al 2017). Temperature was measured using a TX10 digital thermometer (Yokogawa, Tokyo, Japan) with a type K temperature probe (Yokogawa, Tokyo, Japan) at each sampling site.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the Unagi-onsen hot spring (Southern Kyushu Island), we collected a total of 65 samples in May 2014, May 2015, November 2015, and December 2016 as a previous study suggested that Carboxydothermus species are abundant in this environment (Yoneda et al 2013a). In addition, we previously isolated the Carboxydocella strains ULO1 and JDF658 at Unagi-ike lake and the Jiunji-onsen hot spring, respectively (Fukuyama et al 2017). Temperature was measured using a TX10 digital thermometer (Yokogawa, Tokyo, Japan) with a type K temperature probe (Yokogawa, Tokyo, Japan) at each sampling site.…”
Section: Methodsmentioning
confidence: 99%
“…AM4Yes (Sokolova et al 2004b)Active chimneySokolova et al (2004b) Firmicutes (thermophilic) Parageobacillus thermoglucosidasius B4168n.rn.rn.r Parageobacillus thermoglucosidasius C56-YS93n.rn.rn.r Parageobacillus thermoglucosidasius DSM 2542 a Yes (Mohr et al 2018)n.rSuzuki et al (1983) Parageobacillus thermoglucosidasius GT23n.rn.rn.r Parageobacillus thermoglucosidasius NBRC 107763n.rn.rn.r Parageobacillus thermoglucosidasius NCIMB 11955n.rn.rn.r Parageobacillus thermoglucosidasius TG4Yes (Inoue et al 2019b)Marine sedimentInoue et al (2019a) Parageobacillus thermoglucosidasius TM242n.rn.rn.r Parageobacillus thermoglucosidasius TNO-09.020n.rn.rn.r Parageobacillus thermoglucosidasius Y4.1MC1n.rn.rn.r Carboxydocella sp. JDF658Yes (Fukuyama et al 2017)Open-air stream from a hot spring wellFukuyama et al (2017) Carboxydocella sp. ULO1Yes (Fukuyama et al 2017)Sediment of a maar lakeFukuyama et al (2017) Carboxydocella sporoproducens DSM 16521Yes (Slepova et al 2006)Hot springSlepova et al (2006) Carboxydocella thermautotrophica 019…”
Section: Codh–ech Gene Clusters Found In Prokaryotic Genomesmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify that the newly designed primers amplify CODHech genes from environmental samples, we performed amplicon sequencing using these primers with the sediment samples collected from two hot springs (UN and JI), where thermophilic hydrogenogenic carboxydotrophs have been detected or isolated (Fukuyama et al 2017 ; Omae et al 2019 ; Yoneda et al 2012 , 2015 ). PCR amplification was observed for three (F4a_p1, F4c1_p1 and F4c1_p2) and two (F4a_p1 and F4c2_p1) of the six primer sets tested in UN and JI, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Cells of Carboxydocella sp. ULO1 and C. maritimus KKC1 were isolated and maintained in our laboratory (Fukuyama et al 2017 ; Yoneda et al 2013 ). The cells of C. hydrogenoformans Z-2901 and Carboxydocella sp.…”
Section: Methodsmentioning
confidence: 99%